3D hydrogel-based microcapsules as an in vitro model to study tumorigenicity, cell migration and drug resistance. - Ertekin, Özlem; Monavari, Mahshid; Krüger, René; Fuentes Chandia, Miguel Angel; Parma, Beatrice; Letort, Gaelle; Tripal, Philipp; Boccaccini, Aldo R.; Boßerhoff, Anja Katrin; Ceppi, Paolo; Kappelmann-Fenzl, Melanie; Leal-Egaña, Aldo (Acta Biomaterialia, 2022)
In this work, we analyzed the reliability of alginate-gelatin microcapsules as artificial tumor model. These tumor-like scaffolds are characterized by their composition and stiffness (∼25 kPa), and their capability to restrict -but not hinder- cell migration, proliferation and release from confinement. Hydrogel-based microcapsules were initially utilized to detect differences in mechano-sensitivity between MCF7 and MDA-MB-231 breast cancer cells, and the endothelial cell line EA.hy926. Additionally, we used RNA-seq and transcriptomic methods to determine how the culture strategy (i.e. 2D v/s 3D) may pre-set the expression of genes involved in multidrug resistance, being then validated by performing cytotoxicological tests and assays of cell morphology. Our results show that both breast cancer cells can generate elongated multicellular spheroids inside the microcapsules, prior being released (mimicking intravasation stages), a behavior which was not observed in endothelial cells. Further, we demonstrate that cells isolated from 3D scaffolds show resistance to cisplatin, a process which seems to be strongly influenced by mechanical stress, instead of hypoxia. We finally discuss the role played by aneuploidy in malignancy and resistance to anticancer drugs, based on the increased number of polynucleated cells found within these microcapsules. Overall, our outcomes demonstrate that alginate-gelatin microcapsules represent a simple, yet very accurate tumor-like model, enabling us to mimic the most relevant malignant hints described in vivo, suggesting that confinement and mechanical stress need to be considered when studying pathogenicity and drug resistance of cancer cells in vitro. STATEMENT OF SIGNIFICANCE: In this work, we analyzed the reliability of alginate-gelatin microcapsules as an artificial tumor model. These scaffolds are characterized by their composition, elastic properties, and their ability to restrict cell migration, proliferation, and release from confinement. Our results demonstrate four novel outcomes: (i) studying cell migration and proliferation in 3D enabled discrimination between malignant and non-pathogenic cells, (ii) studying the cell morphology of cancer aggregates entrapped in alginate-gelatin microcapsules enabled determination of malignancy degree in vitro, (iii) determination that confinement and mechanical stress, instead of hypoxia, are required to generate clones resistant to anticancer drugs (i.e. cisplatin), and (iv) evidence that resistance to anticancer drugs could be due to the presence of polynucleated cells localized inside polymer-based artificial tumors.

3Dscript: animating 3D/4D microscopy data using a naturallanguage- based syntax. - Palmisano, Ralf; Tripal, Philipp; Schmid, Benjamin; Fraaß, Tina (https://www.quantitativebioimaging.com/qbi2020/conference-and-program-booklet/, 2020)
We introduce a software framework that assembles 3D animations of imaging data using a textual description with a syntax based on natural English language. In contrast to the established key frame based approach, smooth and complex motion sequences are intuitively implemented by concatenating multiple instructions. [1] The syntax is extensible and we demonstrate its integration into existing 3D visualization software. The user typically stores different rendering settings and scene transformations in a number of key frames along a timeline, and the rendering engine creates a smooth animation by interpolating between them. Key frames save the spatial transformation of an object as a state, e.g. three angles for a rotation, and not as a transition. This at least 4 key frames are required to define a 360- degree rotation with constant speed unambiguously. Even more are required if the motion is non-linear, which is essential for achieving smooth and pleasant motions. Software packages therefore typically provide a shortcut to insert key frames for rotations around common axes. More complex motions such as combined rotations around multiple axes, however, are difficult to achieve. The syntax based on natural English language maximizes experience and provides easy access for users of distinct fields. Each instruction is an English sentence. Complex motion sequences are implemented by combining multiple instructions which are applied in the order they appear in the text. The syntax comprises phrases for standard non-linear accelerations, resulting in smooth and natural animations. Self-defined macro functions can be used to define motion and other parameters as functions over time. We provide 3DScript as a Fiji/ImageJ plugin including an hardware-accelerated 3D renderer and a dedicated editor featuring auto-completion and recording. Although tailored to the included rendering engine, both the syntax and our animation framework can be easily adapted by other rendering software.<br
Keywords: 3D Animation; Natural Language Syntax; 3Dscript; Fiji/ImageJ Plug-In

3Dscript: animating 3D/4D microscopy data using a natural-language-based syntax - Schmid, Benjamin; Tripal, Philipp; Fraaß, Tina; Kersten, Christina; Ruder, Barbara; Grüneboom, Anika; Huisken, Jan; Palmisano, Ralf (Nature Methods, 2019)
CRIS-Team WoS Importer:2019-04-09

3Dscript.server: true server-side 3D animation of microscopy images using a natural language-based syntax - Schmid, Benjamin; Tripal, Philipp; Winter, Zoltan; Palmisano, Ralf (Bioinformatics, 2021)
A Summary: Creating 3D animations from microscopy data is computationally expensive and requires high-end hardware. We therefore developed 3Dscript.server, a 3D animation software that runs as a service on dedicated, shared workstations. Using 3Dscript as the underlying rendering engine, it offers unique features not found in existing software: rendering is performed completely server-side. The target animation is specified on the client without the rendering engine, eliminating any hardware requirements client-side. Still, defining an animation is intuitive due to 3Dscript's natural language-based animation description. We implemented a new OMERO web app to utilize 3Dscript.server directly from the OMERO web interface; a Fiji client to use 3Dscript.server from Fiji for integration into image processing pipelines; and batch scripts to run 3Dscript.server on compute clusters for large-scale visualization projects.
CRIS-Team WoS Importer:2022-01-07

Acid sphingomyelinase-ceramide system mediates effects of antidepressant drugs - Gulbins, Erich; Palmada, Monica; Reichel, Martin; Lueth, Anja; Boehmer, Christoph; Amato, Davide; Müller, Christian P.; Tischbirek, Carsten H.; Groemer, Teja W.; Tabatabai, Ghazaleh; Becker, Katrin A.; Tripal, Philipp; et al. (Nature Medicine, 2013)
Major depression is a highly prevalent severe mood disorder that is treated with antidepressants. The molecular targets of antidepressants require definition. We investigated the role of the acid sphingomyelinase (Asm)-ceramide system as a target for antidepressants. Therapeutic concentrations of the antidepressants amitriptyline and fluoxetine reduced Asm activity and ceramide concentrations in the hippocampus, increased neuronal proliferation, maturation and survival and improved behavior in mouse models of stress-induced depression. Genetic Asm deficiency abrogated these effects. Mice overexpressing Asm, heterozygous for acid ceramidase, treated with blockers of ceramide metabolism or directly injected with C16 ceramide in the hippocampus had higher ceramide concentrations and lower rates of neuronal proliferation, maturation and survival compared with controls and showed depression-like behavior even in the absence of stress. The decrease of ceramide abundance achieved by antidepressant-mediated inhibition of Asm normalized these effects. Lowering ceramide abundance may thus be a central goal for the future development of antidepressants.
Created from Fastlane, Scopus look-up

A New Fluorogenic Small-Molecule Labeling Tool for Surface Diffusion Analysis and Advanced Fluorescence Imaging of β-Site Amyloid Precursor Protein-Cleaving Enzyme 1 Based on Silicone Rhodamine: SiR-BACE1 - Karch, Sandra; Broichhagen, Johannes; Schneider, Julia; Boening, Daniel; Hartmann, Stephanie; Schmid, Benjamin; Tripal, Philipp; Palmisano, Ralf; Alzheimer, Christian; Johnsson, Kai; Huth, Tobias (Journal of Medicinal Chemistry, 2018)
β-site APP-cleaving enzyme 1 (BACE1) is a major player in the pathogenesis of Alzheimer's disease. Structural and functional fluorescence microscopy offers a powerful approach to learn about the physiology and pathophysiology of this protease. Up to now, however, common labeling techniques require genetic manipulation, use large antibodies, or are not compatible with live cell imaging. Fluorescent small molecules that specifically bind to the protein of interest can overcome these limitations. Herein, we introduce SiR-BACE1, a conjugate of the BACE1 inhibitor S-39 and SiR647, as a novel fluorogenic, tag-free, and antibody-free label for BACE1. We present its chemical development, characterize its photophysical and pharmacologic properties, and evaluate its behavior in solution, in overexpression systems, and in native brain tissue. We demonstrate its applicability in confocal, stimulated emission depletion and dynamic single-molecule microscopy. The first functional studies with SiR-BACE1 on the surface mobility of BACE1 revealed a markedly confined diffusion pattern.
EVALuna2:35761

Angiostatic immune reaction in colorectal carcinoma: Impact on survival and perspectives for antiangiogenic therapy - Naschberger, Elisabeth; Croner, Roland S.; Merkel, Susanne; Dimmler, Arno; Tripal, Philipp; Amann, Kerstin Ute; Kremmer, Elisabeth; Brueckl, Wolfgang M.; Papadopoulos, Thomas; Hohenadl, Christine; Hohenberger, Werner; Stürzl, Michael (International Journal of Cancer, 2008)
Angiogenesis and inflammation are the 2 major stroma reactions in colorectal carcinoma (CRC). Guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation. Therefore, we hypothesized that GBP-1 may be a biomarker of intrinsic angiostasis associated with an improved outcome in CRC patients. GBP-1 was strongly expressed in endothelial cells and immune cells in the desmoplastic stroma of 32% of CRC as determined by immunohistochemical investigation of 388 sporadic CRC. Cancer-related 5-year survival was highly significant (p < 0.001) increased (16.2%) in patients with GBP-1-positive CRC. Multivariate analysis showed that GBP-1 is an independent prognostic factor indicating a reduction of the relative risk of cancer-related death by the half (p = 0.032). A comparative transcriptome analysis (22,215 probe sets) of GBP-1-positive (n = 12) and -negative (n = 12) tumors showed that particularly IFN-γ-induced genes including the major antiangiogenic chemokines CXCL9, CXCL10 and CXCL11 were coexpressed with GBP-1. Altogether our findings indicated that GBP-1 may be a novel biomarker and an active component of a Th-1-like angiostatic immune reaction in CRC. This reaction may affect patient's response to antiangiogenic therapy and the identification of such tumors may provide a novel criterion for patient selection. Moreover, the induction of a Th-1-like angiostatic immune reaction may be a promising approach for the clinical treatment of CRC. © 2008 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal carcinoma; Guanylate binding protein-1; Inflammation; Interferon-γ

A Novel Magnetic Field Device for Inducing Hyperthermia Using Magnetic Nanoparticles - Dürr, Stephan; Schmidt, Oliver; Janko, Christina; Kraemer, H P; Tripal, Philipp; Eiermann, F; Tietze, R; Lyer, Stefan; Alexiou, Christoph (Biomedizinische Technik, 2013)
A new alternating current (AC) magnetic field applicator was designed to induce hyperthermia in an animal tumour model using superparamagnetic iron oxidenanoparticles (SPION). First experiments on phantoms including different concentrations of SPION were conducted.The results confirmed that the new AC magnetic field applicator could heat-p SPION. This proofs the capability to induce hyperthermia by SPION, dependent on the concentration
EVALuna2:19922
Keywords: Magnetic drug targeting; nanoparticles; alternating current magnetic field; hyperthermia

Application of machine learning algorithms for multiparametric MRI-based evaluation of murine colitis - Ellmann, Stephan; Langer, Victoria; Britzen-Laurent, Nathalie; Hildner, Kai; Huber, Carina; Tripal, Philipp; Seyler, Lisa; Waldner, Maximilian; Uder, Michael; Stürzl, Michael; Bäuerle, Tobias (PLoS ONE, 2018)
Magnetic resonance imaging (MRI) allows non-invasive evaluation of inflammatory bowel disease (IBD) by assessing pathologically altered gut. Besides morphological changes, relaxation times and diffusion capacity of involved bowel segments can be obtained by MRI. The aim of this study was to assess the use of multiparametric MRI in the diagnosis of experimentally induced colitis in mice, and evaluate the diagnostic benefit of parameter combinations using machine learning. This study relied on colitis induction by Dextran Sodium Sulfate (DSS) and investigated the colon of mice in vivo as well as ex vivo. Receiver Operating Characteristics were used to calculate sensitivity, specificity, positive- and negative-predictive values (PPV and NPV) of these single values in detecting DSS-treatment as a reference condition. A Model Averaged Neural Network (avNNet) was trained on the multiparametric combination of the measured values, and its predictive capacity was compared to those of the single parameters using exact binomial tests. Within the in vivo subgroup (n = 19), the avNNet featured a sensitivity of 91.3% (95% CI: 86.6-96.0%), specificity of 92.3% (95% CI: 85.1-99.6%), PPV of 96.9% (94.0-99.9%) and NPV of 80.0% (95% CI: 69.9-90.1%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.003) and performing significantly worse compared to none of the single values. Within the ex vivo subgroup (n = 30), the avNNet featured a sensitivity of 87.4% (95% CI: 82.6-92.2%), specificity of 82.9% (95% CI: 76.1-89.7%), PPV of 88.9% (84.3-93.5%) and NPV of 80.8% (95% CI: 73.8-87.9%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.015), exceeded by none of the single parameters. In experimental mouse colitis, multiparametric MRI and the combination of several single measured values to an avNNet can significantly increase diagnostic accuracy compared to the single parameters alone. This pilot study will provide new avenues for the development of an MR-derived colitis score for optimized diagnosis and surveillance of inflammatory bowel disease.
EVALuna2:35135

A regulatory protein-protein interaction governs glutamate biosynthesis in Bacillus subtilis: The glutamate dehydrogenase RocG moonlights in controlling the transcription factor GltC - Commichau, Fabian M.; Herzberg, Christina; Tripal, Philipp; Valerius, Oliver; Stülke, Jörg (Molecular Microbiology, 2007)
Glutamate synthesis is the link between carbon and nitrogen metabolism. In Bacillus subtilis, glutamate is exclusively synthesized by the glutamate synthase encoded by the gltAB operon. The glutamate dehydrogenase RocG from B. subtilis is exclusively devoted to glutamate degradation rather than to its synthesis. The expression of the gltAB operon is induced by glucose and ammonium and strongly repressed by arginine. Regulation by glucose and arginine depends on the transcriptional activator protein GltC. The gltAB operon is constitutively expressed in a rocG mutant strain, but the molecular mechanism of negative control of gltAB expression by RocG has so far remained unknown. We studied the role of RocG in the intracellular accumulation of GltC. Furthermore, we considered the possibility that RocG might act as a transcription factor and be able to inhibit the expression of gltAB either by binding to the mRNA or to the promoter region of the gltAB operon. Finally, we asked whether a direct binding of RocG to GltC could be responsible for the inhibition of GltC. The genetic and biochemical data presented here show that the glutamate dehydrogenase RocG is able to bind to and concomitantly inactivate the activator protein GltC. This regulatory mechanism by the bifunctional enzyme RocG allows the tight control of glutamate metabolism by the availability of carbon and nitrogen sources. © 2007 The Authors.
Created from Fastlane, Scopus look-up

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

A Stat6/Pten Axis Links Regulatory T Cells with Adipose Tissue Function - Kaelin, Stefanie; Becker, Maike; Ott, Verena B.; Serr, Isabelle; Hosp, Fabian; Mollah, Mohammad M. H.; Keipert, Susanne; Lamp, Daniel; Rohner-Jeanrenaud, Francoise; Flynn, Victoria K.; Scherm, Martin G.; Nascimento, Lucas F. R.; et al. (Cell Metabolism, 2017)
Obesity and type 2 diabetes are associated with metabolic defects and adipose tissue inflammation. Foxp3+ regulatory T cells (Tregs) control tissue homeostasis by counteracting local inflammation. However, if and how T cells interlink environmental influences with adipocyte function remains unknown. Here, we report that enhancing sympathetic tone by cold exposure, beta3-adrenergic receptor (ADRB3) stimulation or a short-term high-calorie diet enhances Treg induction in vitro and in vivo. CD4+ T cell proteomes revealed higher expression of Foxp3 regulatory networks in response to cold or ADRB3 stimulation in vivo reflecting Treg induction. Specifically, Ragulator-interacting protein C17orf59, which limits mTORC1 activity, was upregulated in CD4+ T cells by either ADRB3 stimulation or cold exposure, suggesting contribution to Treg induction. By loss- and gain-of-function studies, including Treg depletion and transfers in vivo, we demonstrated that a T cell-specific Stat6/Pten axis links cold exposure or ADRB3 stimulation with Foxp3+ Treg induction and adipose tissue function. Our findings offer a new mechanistic model in which tissue-specific Tregs maintain adipose tissue function.
EVALuna2:33893

B Cell Speed and B-FDC Contacts in Germinal Centers Determine Plasma Cell Output via Swiprosin-1/EFhd2 - Reimer, Dorothea; Meyer-Hermann, Michael; Rakhymzhan, Asylkhan; Steinmetz, Tobit; Tripal, Philipp; Thomas, Jana; Böttcher, Martin; Mougiakakos, Dimitrios; Schulz, Sebastian; Urbanczyk, Sophia; Hauser, Anja E.; Niesner, Raluca A.; et al. (Cell Reports, 2020)
Plasma cells secreting affinity-matured antibodies develop in germinal centers (GCs), where B cells migrate persistently and directionally over defined periods of time. How modes of GC B cell migration influence plasma cell development remained unclear. Through genetic deletion of the F-actin bundling protein Swiprosin-1/EF-hand domain family member 2 (EFhd2) and by two-photon microscopy, we show that EFhd2 restrains B cell speed in GCs and hapten-specific plasma cell output. Modeling the GC reaction reveals that increasing GC B cell speed promotes plasma cell generation. Lack of EFhd2 also reduces contacts of GC B cells with follicular dendritic cells in vivo. Computational modeling uncovers that both GC output and antibody affinity depend quantitatively on contacts of GC B cells with follicular dendritic cells when B cells migrate more persistently. Collectively, our data explain how GC B cells integrate speed and persistence of cell migration with B cell receptor affinity.
CRIS-Team Scopus Importer:2020-08-14
Keywords: actin cytoskeleton; B cell receptor; differentiation; follicular dendritic cell; germinal center; migration; plasma cell; selection; Swiprosin-1/EFhd2; synapse

Cellular Mechanisms of Etrolizumab Treatment in Inflammatory Bowel Disease - Lichnog, Charlotte; Klabunde, Sha; Becker, Emily; Fuh, Franklin; Tripal, Philipp; Atreya, Raja; Klenske, Entcho; Erickson, Rich; Chiu, Henry; Reed, Chae; Chung, Shan; Neufert, Clemens; et al. (Frontiers in Pharmacology, 2019)
Background: Anti-integrin therapy is a new frontline strategy in the treatment of inflammatory bowel diseases (IBD). The anti-beta 7 integrin antibody etrolizumab is currently being investigated for safety and efficacy in Crohn's disease (CD) and ulcerative colitis (UC) in several phase III trials. Mechanistically, etrolizumab is known to block beta 7 integrin ligand binding and reduces intestinal trafficking of beta 7-expressing cells. Etrolizumab blocks beta 7 integrin ligand binding and reduces beta 7-positive lymphocyte migration and retention in the inflamed gut mucosa, but the exact mechanisms by which this inhibition occurs are not fully understood.
CRIS-Team WoS Importer:2019-02-21

Characterization of Bacillus subtilis mutants with carbon source-independent glutamate biosynthesis - Commichau, Fabian M.; Wacker, Ingrid; Schleider, Jan; Blencke, Hans-Matti; Reif, Irene; Tripal, Philipp; Stülke, Jörg (Journal of Molecular Microbiology and Biotechnology, 2006)
Bacillus subtilis synthesizes glutamate from 2-oxoglutarate and glutamine using the glutamate synthase, encoded by the gltAB operon. Glutamate degradation involves the catabolic glutamate dehydrogenase (GDH) RocG. Expression of both gltAB and rocG is controlled by the carbon and nitrogen sources. In the absence of glucose or other well-metabolizable carbon sources, B. subtilis is unable to grow unless provided with external glutamate. In this work, we isolated mutations that suppressed this growth defect of B. subtilis on minimal media (sgd mutants). All mutations enabled the cells to express the gltAB operon even in the absence of glucose. The mutations were all identified in the rocG gene suggesting that the catabolic GDH is essential for controlling gltAB expression in response to the availability of sugars. Copyright © 2007 S. Karger AG.
Created from Fastlane, Scopus look-up
Keywords: Bacillus subtilis; Catabolite regulation; Glutamate dehydrogenase; Glutamate synthase

Derivatization of common antidepressant drugs increases inhibition of acid sphingomyelinase and reduces induction of phospholipidosis - Rhein, Cosima; Löber, Stefan; Gmeiner, Peter; Gulbins, Erich; Tripal, Philipp; Kornhuber, Johannes (Journal of Neural Transmission, 2018)
Keywords: Desipramine; Fluoxetine; Acid sphingomyelinase; Major depression; Phospholipidosis; Functional inhibitors of ASM activity (FIASMAs); Imipramine

Drug-induced phospholipidosis caused by combinations of common drugs in vitro - Glock, Mareike; Mühlbacher, Markus; Hurtig, Henoch; Tripal, Philipp; Kornhuber, Johannes (Toxicology in Vitro, 2016)
Drug-induced phospholipidosis (DIPLD), characterized by the accumulation of phospholipids within lysosomes, is suspected to impair lysosomal function and considered an adverse side effect of the administered medication. The increasing use of polypharmacy and the resultant elevated risks of adverse drug reactions raise the need to explore the effects of drug combinations with respect to their influence on side effects, such as DIPLD. In this study, we utilized an in vitro assay to investigate DIPLD that was caused by 24 commonly used drugs applied alone and in binary combinations with each other. Moreover, we attempted to predict the extent of DIPLD resulting from the combinations using a simple additive approach based on the increase in phospholipid levels caused by the single drugs. The results suggest that DIPLD, which was caused by combinations of drugs, occurs in an additive manner, depending on total drug concentration. Furthermore, we show that the extent of DIPLD can be predicted from the DIPLD caused by the single drugs. Thus, the simultaneous use of multiple drugs with PLD-inducing properties increases the event risk, as well as the severity of drug-induced phospholipidosis. The findings underline the importance of considering the DIPLD-inducing properties of drugs, especially in the context of polypharmacy.
EVALuna2:23782

Dynamic imaging of iel-iec co-cultures allows for quantification of cd103-dependent t cell migration - Enderle, Karin; Dinkel, Martin; Spath, Eva-Maria; Schmid, Benjamin; Zundler, Sebastian; Tripal, Philipp; Neurath, Markus; Hildner, Kai; Neufert, Clemens (International Journal of Molecular Sciences, 2021)
Intraepithelial lymphocytes (IEL) are widely distributed within the small intestinal epithelial cell (IEC) layer and represent one of the largest T cell pools of the body. While implicated in the pathogenesis of intestinal inflammation, detailed insight especially into the cellular cross-talk between IELs and IECs is largely missing in part due to lacking methodologies to monitor this interaction. To overcome this shortcoming, we employed and validated a murine IEL-IEC (organoids) ex vivo co-culture model system. Using livecell imaging we established a protocol to visualize and quantify the spatio-temporal migratory behavior of IELs within organoids over time. Applying this methodology, we found that IELs lacking CD103 (i.e., integrin alpha E, ITGAE) surface expression usually functioning as a retention receptor for IELs through binding to E-cadherin (CD324) expressing IECs displayed aberrant mobility and migration patterns. Specifically, CD103 deficiency affected the ability of IELs to migrate and reduced their speed during crawling within organoids. In summary, we report a new technology to monitor and quantitatively assess especially migratory characteristics of IELs communicating with IEC ex vivo. This approach is hence readily applicable to study the effects of targeted therapeutic interventions on IEL-IEC cross-talk.
CRIS-Team Scopus Importer:2021-05-21
Keywords: CD103; Intestinal organoids; Intraepithelial lymphocytes; Life cell imaging; Lympho-cyte migration

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Flow cytometry for intracellular SPION quantification: specificity and sensitivity in comparison with spectroscopic methods - Friedrich, Ralf P.; Janko, Christina; Poettler, Marina; Tripal, Philipp; Zaloga, Jan; Cicha, Iwona; Dürr, Stephan; Nowak, Johannes; Odenbach, Stefan; Slabu, Ioana; Liebl, Maik; Trahms, Lutz; et al. (International Journal of Nanomedicine, 2015)
Due to their special physicochemical properties, iron nanoparticles offer new promising possibilities for biomedical applications. For bench to bedside translation of super-paramagnetic iron oxide nanoparticles (SPIONs), safety issues have to be comprehensively clarified. To understand concentration-dependent nanoparticle-mediated toxicity, the exact quantification of intracellular SPIONs by reliable methods is of great importance. In the present study, we compared three different SPION quantification methods (ultraviolet spectrophotometry, magnetic particle spectroscopy, atomic adsorption spectroscopy) and discussed the shortcomings and advantages of each method. Moreover, we used those results to evaluate the possibility to use flow cytometric technique to determine the cellular SPION content. For this purpose, we correlated the side scatter data received from flow cytometry with the actual cellular SPION amount. We showed that flow cytometry provides a rapid and reliable method to assess the cellular SPION content. Our data also demonstrate that internalization of iron oxide nanoparticles in human umbilical vein endothelial cells is strongly dependent to the SPION type and results in a dose-dependent increase of toxicity. Thus, treatment with lauric acid-coated SPIONs (SEON(LA)) resulted in a significant increase in the intensity of side scatter and toxicity, whereas SEON(LA) with an additional protein corona formed by bovine serum albumin (SEON(LA-BSA)) and commercially available Rienso(®) particles showed only a minimal increase in both side scatter intensity and cellular toxicity. The increase in side scatter was in accordance with the measurements for SPION content by the atomic adsorption spectroscopy reference method. In summary, our data show that flow cytometry analysis can be used for estimation of uptake of SPIONs by mammalian cells and provides a fast tool for scientists to evaluate the safety of nanoparticle products.
EVALuna2:19955

Fluorescent Labeling and 2-Photon Imaging of Mouse Tooth Pulp Nociceptors - Kadala, A.; Sotelo-Hitschfeld, Pamela; Ahmad, Ziad; Tripal, Philipp; Schmid, Benjamin; Mueller, A.; Bernal, L.; Winter, Zoltan; Brauchi, S.; Lohbauer, Ulrich; Meßlinger, Karl; Lennerz, J. K.; et al. (Journal of Dental Research, 2017)
Retrograde fluorescent labeling of dental primary afferent neurons (DPANs) has been described in rats through crystalline fluorescent DiI, while in the mouse, this technique was achieved with only Fluoro-Gold, a neurotoxic fluorescent dye with membrane penetration characteristics superior to the carbocyanine dyes. We reevaluated this technique in the rat with the aim to transfer it to the mouse because comprehensive physiologic studies require access to the mouse as a model organism. Using conventional immunohistochemistry, we assessed in rats and mice the speed of axonal dye transport from the application site to the trigeminal ganglion, the numbers of stained DPANs, and the fluorescence intensity via 1) conventional crystalline DiI and 2) a novel DiI formulation with improved penetration properties and staining efficiency. A 3-dimensional reconstruction of an entire trigeminal ganglion with 2-photon laser scanning fluorescence microscopy permitted visualization of DPANs in all 3 divisions of the trigeminal nerve. We quantified DPANs in mice expressing the farnesylated enhanced green fluorescent protein (EGFPf) from the transient receptor potential cation channel subfamily M member 8 (TRPM8EGFPf/+) locus in the 3 branches. We also evaluated the viability of the labeled DPANs in dissociated trigeminal ganglion cultures using calcium microfluorometry, and we assessed the sensitivity to capsaicin, an agonist of the TRPV1 receptor. Reproducible DiI labeling of DPANs in the mouse is an important tool 1) to investigate the molecular and functional specialization of DPANs within the trigeminal nociceptive system and 2) to recognize exclusive molecular characteristics that differentiate nociception in the trigeminal system from that in the somatic system. A versatile tool to enhance our understanding of the molecular composition and characteristics of DPANs will be essential for the development of mechanism-based therapeutic approaches for dentine hypersensitivity and inflammatory tooth pain.
EVALuna2:24704

Functional implications of novel human acid sphingomyelinase splice variants - Rhein, Cosima; Tripal, Philipp; Seebahn, Angela; Konrad, Alice; Kramer, Marcel; Nagel, Christine; Kemper, Jonas; Bode, Jens; Mühle, Christiane; Gulbins, Erich; Reichel, Martin; Becker, Cord-Michael; et al. (PLoS ONE, 2012)
Acid sphingomyelinase (ASM) hydrolyses sphingomyelin and generates the lipid messenger ceramide, which mediates a variety of stress-related cellular processes. The pathological effects of dysregulated ASM activity are evident in several human diseases and indicate an important functional role for ASM regulation. We investigated alternative splicing as a possible mechanism for regulating cellular ASM activity.We identified three novel ASM splice variants in human cells, termed ASM-5, -6 and -7, which lack portions of the catalytic- and/or carboxy-terminal domains in comparison to full-length ASM-1. Differential expression patterns in primary blood cells indicated that ASM splicing might be subject to regulatory processes. The newly identified ASM splice variants were catalytically inactive in biochemical in vitro assays, but they decreased the relative cellular ceramide content in overexpression studies and exerted a dominant-negative effect on ASM activity in physiological cell models.These findings indicate that alternative splicing of ASM is of functional significance for the cellular stress response, possibly representing a mechanism for maintaining constant levels of cellular ASM enzyme activity.
EVALuna2:4672

Functional inhibitors of acid sphingomyelinase (FIASMAS): A novel pharmacological group of drugs with broad clinical applications - Kornhuber, Johannes; Tripal, Philipp; Reichel, Martin; Mühle, Christiane; Rhein, Cosima; Muehlbacher, Markus; Groemer, Teja W.; Gulbins, Erich (Cellular Physiology and Biochemistry, 2010)
Acid sphingomyelinase (ASM) is an important lipid-metabolizing enzyme cleaving sphingomyelin to ceramide, mainly within lysosomes. Acid ceramidase (AC) further degrades ceramide to sphingosine which can then be phosphorylated to sphingosine-1-phosphate. Ceramide and its metabolite sphingosine-1-phosphate have been shown to antagonistically regulate apoptosis, cellular differentiation, proliferation and cell migration. Inhibitors of ASM or AC therefore hold promise for a number of new clinical therapies, e.g. for Alzheimer's disease and major depression on the one hand and cancer on the other. Inhibitors of ASM have been known for a long time. Cationic amphiphilic substances induce the detachment of ASM protein from inner lysosomal membranes with its consecutive inactivation, thereby working as functional inhibitors of ASM. We recently experimentally identified a large number of hitherto unknown functional inhibitors of ASM and determined specific physicochemical properties of such cationic amphiphilic substances that functionally inhibit ASM. We propose the acronym "FIASMA" (Functional Inhibitor of Acid SphingoMyelinAse) for members of this large group of compounds with a broad range of new clinical indications. FIASMAs differ markedly with respect to molecular structure and current clinical indication. Most of the available FIASMAs are licensed for medical use in humans, are minimally toxic and may therefore be applied for disease states associated with increased activity of ASM. Copyright © 2010 S. Karger AG, Basel.
Created from Fastlane, Scopus look-up
Keywords: Acid ceramidase; Acid sphingomyelinase; Acid trapping; Cationic amphiphilic drugs; Desipramine; Lysosomotropism

Functional Inhibitors of Acid Sphingomyelinase (FIASMAs) - Kornhuber, Johannes; Tripal, Philipp; Gulbins, Erich; Mühlbacher, Markus (Sphingolipids: Basic Science and Drug Development, 2013)
Sphingolipids are not only structural components of biological membranes, but also play an important role in cellular signalling and, thus, are involved in cell proliferation and differentiation but also stress and cell death. It is therefore of great clinical relevance to define inhibitors of the enzymes involved in sphingolipid metabolism. Here, we describe the state of the art of functional inhibitors of the acid sphingomyelinase. The acid sphingomyelinase converts sphingomyelin to ceramide, a compound often involved in cell stress. We describe the structural and physicochemical properties, the distribution, the pharmacokinetics, the pharmocodynamics and the clinical use of direct and functional inhibitors of the acid sphingomyelinase.<br
Keywords: Acid sphingomyelinaseö; Functional inhibitors; Ceramide; Structure–property-activity relation

Guanylate binding protein-1 inhibits spreading and migration of endothelial cells through induction of integrin α4 expression - Weinlaender, Kristina; Naschberger, Elisabeth; Lehmann, Michael H.; Tripal, Philipp; Paster, Wolfgang; Stockinger, Hannes; Hohenadl, Christine; Stürzl, Michael (The FASEB Journal, 2008)
Human guanylate binding protein-1 (GBP-1) is a large GTPase that is induced by inflammatory cytokines and acts antiangiogenically through the inhibition of endothelial cell proliferation and migration. In this study, we detected that GBP-1-expressing cells show a significantly reduced spreading and migration on fibronectin matrices. Investigating possible mechanisms of these effects, we found that integrin α4 (ITGA4) was consistently up-regulated at both the RNA and protein level in GBP-1-expressing cell cultures. Inhibition of cell spreading and migration by GBP-1 was dependent on the binding of ITGA4 to fibronectin. The inflammatory cytokines IL-1β and TNF-α induced ITGA4 expression in HUVECs and inhibited spreading and migration. Knockdown of GBP-1 by shRNA abrogated inflammatory cytokine induced ITGA4 expression and restored spreading and migration capabilities of the cells. These results show that inhibition of endothelial cell spreading and migration by inflammatory cytokines is mediated by GBP-1 through induction of ITGA4 expression. Endothelial cell migration is a key process during angiogenesis. Therefore, ITGA4 may be a novel molecular target to modulate angiogenesis in human disease. © FASEB.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Inflammation; Integrins; Large GTPase

Identification of Drugs Inducing Phospholipidosis by Novel in vitro Data - Muehlbacher, Markus; Tripal, Philipp; Roas, Florian; Kornhuber, Johannes (ChemMedChem, 2012)
Drug-induced phospholipidosis (PLD) is a lysosomal storage disorder characterized by the accumulation of phospholipids within the lysosome. This adverse drug effect can occur in various tissues and is suspected to impact cellular viability. Therefore, it is important to test chemical compounds for their potential to induce PLD during the drug design process. PLD has been reported to be a side effect of many commonly used drugs, especially those with cationic amphiphilic properties. To predict drug-induced PLD in silico, we established a high-throughput cell-culture-based method to quantitatively determine the induction of PLD by chemical compounds. Using this assay, we tested 297 drug-like compounds at two different concentrations (2.5μM and 5.0μM). We were able to identify 28 previously unknown PLD-inducing agents. Furthermore, our experimental results enabled the development of a binary classification model to predict PLD-inducing agents based on their molecular properties. This random forest prediction system yields a bootstrapped validated accuracy of 86%. PLD-inducing agents overlap with those that target similar biological processes; a high degree of concordance with PLD-inducing agents was identified for cationic amphiphilic compounds, small molecules that inhibit acid sphingomyelinase, compounds that cross the blood-brain barrier, and compounds that violate Lipinski's rule of five. Furthermore, we were able to show that PLD-inducing compounds applied in combination additively induce PLD. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Created from Fastlane, Scopus look-up
Keywords: Cationic amphiphilic drugs; Lysosomal storage disorders; Phospholipidosis; Phospholipids; Toxicology

Identification of new functional inhibitors of acid sphingomyelinase using a structure-property-activity relation model - Kornhuber, Johannes; Tripal, Philipp; Reichel, Martin; Terfloth, Lothar; Bleich, Stefan; Wiftfang, Jens; Gulbins, Erich (Journal of Medicinal Chemistry, 2008)
Some organic weak bases induce a detachment from inner lysosomal membranes and subsequent inactivation of acid sphingomyelinase (ASM) and thus work as functional ASM inhibitors. The aim of the present investigation was to develop a structure-property-activity relation (SPAR) model in order to specify the structural and physicochemical characteristics of probes capable of functionally inhibiting ASM. High pKa and high log P values are necessary but not sufficient preconditions for functional inhibition of ASM. The experimental data supported the requirement of an additional factor, which is necessary for functional inhibition of ASM. This factor k is related to the steric hindrance of the most basic nitrogen atom and presumably modulates the free presentation of a protonated nitrogen atom at the inner lysosomal surface. During the course of the study, we characterized 26 new functional ASM inhibitors, including doxepine 63, fluoxetine 104, maprotiline 109, nortriptyline 114, paroxetine 118, sertraline 124, suloctidil 125, and terfenadine 127. © 2008 American Chemical Society.
Created from Fastlane, Scopus look-up

Identification of novel functional inhibitors of acid sphingomyelinase - Kornhuber, Johannes; Muehlbacher, Markus; Trapp, Stefan; Pechmann, Stefanie; Friedl, Astrid; Reichel, Martin; Mühle, Christiane; Terfloth, Lothar; Groemer, Teja W.; Spitzer, Gudrun M.; Liedl, Klaus R.; Gulbins, Erich; et al. (PLoS ONE, 2011)
We describe a hitherto unknown feature for 27 small drug-like molecules, namely functional inhibition of acid sphingomyelinase (ASM). These entities named FIASMAs (Functional Inhibitors of Acid SphingoMyelinAse), therefore, can be potentially used to treat diseases associated with enhanced activity of ASM, such as Alzheimer's disease, major depression, radiation- and chemotherapy-induced apoptosis and endotoxic shock syndrome. Residual activity of ASM measured in the presence of 10 μM drug concentration shows a bimodal distribution; thus the tested drugs can be classified into two groups with lower and higher inhibitory activity. All FIASMAs share distinct physicochemical properties in showing lipophilic and weakly basic properties. Hierarchical clustering of Tanimoto coefficients revealed that FIASMAs occur among drugs of various chemical scaffolds. Moreover, FIASMAs more frequently violate Lipinski's Rule-of-Five than compounds without effect on ASM. Inhibition of ASM appears to be associated with good permeability across the blood-brain barrier. In the present investigation, we developed a novel structure-property-activity relationship by using a random forest-based binary classification learner. Virtual screening revealed that only six out of 768 (0.78%) compounds of natural products functionally inhibit ASM, whereas this inhibitory activity occurs in 135 out of 2028 (6.66%) drugs licensed for medical use in humans. © 2011 Kornhuber et al.
Created from Fastlane, Scopus look-up

IFN-γ drives inflammatory bowel disease pathogenesis through VE-cadherin-directed vascular barrier disruption - Langer, Victoria; Vivi, Eugenia; Regensburger, Daniela; Winkler, Thomas; Waldner, Maximilian; Rath, Timo; Schmid, Benjamin; Skottke, Lisa; Lee, Somin; Jeon, Noo Li; Wohlfahrt, Thomas; Kramer, Viktoria; et al. (Journal of Clinical Investigation, 2019)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder with rising incidence. Diseased tissues are heavily vascularized. Surprisingly, the pathogenic impact of the vasculature in IBD and the underlying regulatory mechanisms remain largely unknown. IFN-γ is a major cytokine in IBD pathogenesis, but in the context of the disease, it is almost exclusively its immune-modulatory and epithelial cell-directed functions that have been considered. Recent studies by our group demonstrated that IFN-γ also exerts potent effects on blood vessels. Based on these considerations, we analyzed the vessel-directed pathogenic functions of IFN-γ and found that it drives IBD pathogenesis through vascular barrier disruption. Specifically, we show that inhibition of the IFN-γ response in vessels by endothelial-specific knockout of IFN-γ receptor 2 ameliorates experimentally induced colitis in mice. IFN-γ acts pathogenic by causing a breakdown of the vascular barrier through disruption of the adherens junction protein VE-cadherin. Notably, intestinal vascular barrier dysfunction was also confirmed in human IBD patients, supporting the clinical relevance of our findings. Treatment with imatinib restored VE-cadherin/adherens junctions, inhibited vascular permeability, and significantly reduced colonic inflammation in experimental colitis. Our findings inaugurate the pathogenic impact of IFN-γ-mediated intestinal vessel activation in IBD and open new avenues for vascular-directed treatment of this disease.

Imaging modalities using magnetic nanoparticles - overview of the developments in recent years - Schwarz, Marc; Dörfler, Arnd; Engelhorn, Tobias; Struffert, Tobias; Tietze, Rainer; Janko, Christina; Tripal, Philipp; Cicha, Iwona; Dürr, Stephan; Alexiou, Christoph; Lyer, Stefan (Nanotechnology Reviews, 2013)
The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of "theranostics" combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparticles as well as their development and potential application in recent years. Furthermore, it describes the research on classic imaging modalities as well as on new techniques to image nanoparticles in vivo and focuses on magnetic-based imaging modalities.
EVALuna2:19967

Impaired Transmigration of Myeloid-Derived Suppressor Cells across Human Sinusoidal Endothelium Is Associated with Decreased Expression of CD13 - Resheq, Yazid J.; Menzner, Ann-Katrin; Bosch, Jacobus J.; Tickle, Joseph; Li, Ka-Kit; Wilhelm, Annika; Hepburn, Elizabeth; Murihead, Gillian; Ward, Stephen T.; Curbishley, Stuart M.; Zimmermann, Henning W.; Bruns, Tony; et al. (Journal of Immunology, 2017)
Human monocytic myeloid-derived suppressor cells (MO-MDSCs) within the hepatic compartment suppress inflammation and impair immune surveillance in liver cancer. It is currently not known whether recruitment of MO-MDSCs from blood via hepatic sinusoidal endothelium (HSEC) contributes to their enrichment within the hepatic compartment. We compared the transmigratory potential of MO-MDSCs and monocytes after adhesion to hepatic endothelial monolayers in flow-based assays that mimic in vivo shear stress in the sinusoids. Despite comparable binding to HSEC monolayers, proportionally fewer MO-MDSCs underwent transendothelial migration, indicating that the final steps of extravasation, where actin polymerization plays an important role, are impaired in MO-MDSCs. In this article, we found reduced levels of CD13 on MO-MDSCs, which has recently been reported to control cell motility in monocytes, alongside reduced VLA-4 expression, an integrin predominantly involved in adherence to the apical side of the endothelium. CD13 and VLA-4 blocking and activating Abs were used in flow-based adhesion assays, live-cell imaging of motility, and actin polymerization studies to confirm a role for CD13 in impaired MO-MDSC transmigration. These findings indicate that CD13 significantly contributes to tissue infiltration by MO-MDSCs and monocytes, thereby contributing to the pathogenesis of hepatic inflammation.
EVALuna2:25713

Improved radiosynthesis and preliminary in vivo evaluation of a 18F-labeled glycopeptide-peptoid hybrid for PET imaging of neurotensin receptor 2 - Maschauer, Simone; Greff, Cornelia; Einsiedel, Jürgen; Ott, Julian; Tripal, Philipp; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (Bioorganic & Medicinal Chemistry, 2015)
UnivIS-Import:2015-04-14:Pub.2015.nat.dchph.lphch.improv

Increased acid sphingomyelinase activity in peripheral blood cells of acutely intoxicated patients with alcohol dependence - Reichel, Martin; Greiner, Elisabeth; Richter-Schmidinger, Tanja; Yedibela, Oezlem; Tripal, Philipp; Jacobi, Andrea; Bleich, Stefan; Gulbins, Erich; Kornhuber, Johannes (Alcoholism-Clinical and Experimental Research, 2010)
Background: Acid sphingomyelinase (ASM; EC 3.1.4.12) hydrolyses membrane sphingomyelin into the bioactive lipid ceramide and is thus involved in different cellular processes such as differentiation, immunity, or cell death. Activation of ASM has been reported in particular in conjunction with the cellular stress response to several external stimuli, and increased ASM activity was observed in a variety of human diseases. Ethanol-induced activation of ASM has been observed in different cell culture systems, thus raising the question about the effect of alcohol intoxication in human subjects on ASM activity in vivo. Methods: We determined ASM activity in peripheral blood mononucleated cells of 27 patients suffering from alcohol dependence. Patients were classified according to their blood alcohol concentration at admission, and ASM activity was determined repeatedly from all patients during alcohol withdrawal. Results: Acutely intoxicated patients displayed significantly higher ASM activity than patients in early abstinence (Mann-Whitney U test: Z = - 2.6, p = 0.009). ASM activity declined in acutely intoxicated patients to normal values with the transition from the intoxicated state to early abstinence (Wilcoxon test: Z = -2.7, p = 0.007). At the end of withdrawal, ASM activity was significantly increased again compared to the early phase of abstinence in both patient groups (Wilcoxon test: Z = -2.691, p = 0.007 and Z = -2.275, p = 0.023, respectively). Conclusions: Alcohol-induced activation of ASM occurs in human subjects and might be responsible for deleterious effects of ethanol intoxication. Chronic alcohol abuse may induce deregulation of sphingomyelin metabolism in general, and this impairment may cause side effects during withdrawal from alcohol. © 2009 by the Research Society on Alcoholism.
Created from Fastlane, Scopus look-up
Keywords: Alcohol Dependence; Ceramide; Sphingomyelin; Sphingomyelin Phosphodiesterase; Sphingomyelinase

Inflammatory activation of the FcγR and IFNγR pathways co-influences the differentiation and activity of osteoclasts - Grötsch, Bettina; Schachtschabel, Elisabeth; Tripal, Philipp; Schmid, Benjamin; Smith, Ana-Suncana; Schett, Georg; Bozec, Aline (Frontiers in Immunology, 2022)
Osteoclasts are polykaryons formed by cell–cell fusion of highly motile progenitors of the myeloid lineage. Osteoclast activity can preserve skeletal strength and bone homeostasis. However, osteoclasts are responsible for bone destruction in rheumatoid arthritis (RA). Fc receptors activated by IgG immune complexes (IC) can boost osteoclast differentiation and bone loss in the course of RA. In contrast, interferon (IFN) γ secreted by immune cells blocks osteoclast activation. Despite their hypothetical importance in the regulation of osteoclast differentiation in RA, the interconnection between the two pathways has not been described so far. Here, we show by total internal reflection fluorescence (TIRF) microscopy that FcγR3 and IFNγ receptor (IFNγR) locate at close vicinity to each other on the human osteoclast surface. Moreover, the average distance increases during the differentiation process. Interestingly, FcγR and IFNγR activation shapes the position of both receptors to each other. Surprisingly, the inhibitory action of IFNγ on in-vitro human osteoclast differentiation depends on the osteoclast differentiation stage. Indeed, IFNγR activation in early osteoclast precursors completely inhibits the formation of polynucleated osteoclasts, while in premature osteoclasts, it further enhanced their fusion. In addition, gene expression analyses showed that IFNγR activation on early precursor cells but not on premature osteoclasts could induce FcγR expression, suggesting a co-regulation of both receptors on human osteoclast precursors. Phosphokinase array data of precursor cells demonstrate that the observed divergence of IFNγR signaling is dependent on the mitogen−activated protein kinase (MAPK) downstream signaling pathway. Overall, our data indicate that FcγR and IFNγR signaling pathways co-influence the differentiation and activity of osteoclasts dependent on the differentiation state, which might reflect the different stages in RA.
CRIS-Team Scopus Importer:2022-10-07
Keywords: FcγR3; IFNγR; IFNγR signaling; ITAM signaling; Osteoclast; rheumatoid arthritis (RA)

Investigating Intestinal Barrier Breakdown in Living Organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Becker, Christoph; Palmisano, Ralf; Stürzl, Michael; Tripal, Philipp (Journal of Visualized Experiments, 2020)
Organoids and three-dimensional (3D) cell cultures allow the investigation of complex biological mechanisms and regulations in vitro, which previously was not possible in classical cell culture monolayers. Moreover, monolayer cell cultures are good in vitro model systems but do not represent the complex cellular differentiation processes and functions that rely on 3D structure. This has so far only been possible in animal experiments, which are laborious, time consuming, and hard to assess by optical techniques. Here we describe an assay to quantitatively determine the barrier integrity over time in living small intestinal mouse organoids. To validate our model, we applied interferon gamma (IFN-gamma) as a positive control for barrier destruction and organoids derived from IFN-gamma receptor 2 knock out mice as a negative control. The assay allowed us to determine the impact of IFN-gamma on the intestinal barrier integrity and the IFN-gamma induced degradation of the tight junction proteins claudin-2, -7, and -15. This assay could also be used to investigate the impact of chemical compounds, proteins, toxins, bacteria, or patient-derived probes on the intestinal barrier integrity.
CRIS-Team WoS Importer:2020-04-17

In vivo monitoring of the antiangiogenic effect of neurotensin receptor-mediated radiotherapy by small-animal positron emission tomography: A pilot study - Maschauer, Simone; Ruckdeschel, Tina; Tripal, Philipp; Haubner, Roland; Einsiedel, Jürgen; Hübner, Harald; Gmeiner, Peter; Kuwert, Torsten; Prante, Olaf (Pharmaceuticals, 2014)
The neurotensin receptor (NTS1) has emerged as an interesting target for molecular imaging and radiotherapy of NTS-positive tumors due to the overexpression in a range of tumors. The aim of this study was to develop a Lu-labeled NTS1 radioligand, its application for radiotherapy in a preclinical model and the imaging of therapy success by small-animal positron emission tomography (μPET) using [Ga]DOTA-RGD as a specific tracer for imaging angiogenesis. The Lu-labeled peptide was subjected to studies on HT29-tumor-bearing nude mice in vivo, defining four groups of animals (single dose, two fractionated doses, four fractionated doses and sham-treated animals). Body weight and tumor diameters were determined three times per week. Up to day 28 after treatment, μPET studies were performed with [Ga]DOTA-RGD. At days 7-10 after treatment with four fractionated doses of 11-14 MBq (each at days 0, 3, 6 and 10), the tumor growth was slightly decreased in comparison with untreated animals. Using a single high dose of 51 MBq, a significantly decreased tumor diameter of about 50% was observed with the beginning of treatment. Our preliminary PET imaging data suggested decreased tumor uptake values of [Ga]DOTA-RGD in treated animals compared to controls at day 7 after treatment. This pilot study suggests that early PET imaging with [Ga]DOTA-RGD in radiotherapy studies to monitor integrin expression could be a promising tool to predict therapy success in vivo. Further successive PET experiments are needed to confirm the significance and predictive value of RGD-PET for NTS-mediated radiotherapy. © 2014 by the authors; licensee MDPI, Basel, Switzerland.

In vivo monitoring of the anti-angiogenic therapeutic effect of the pan-deacetylase inhibitor panobinostat by small animal PET in a mouse model of gastrointestinal cancers - Maschauer, Simone; Gahr, Susanne; Gandesiri, Muktheshwar; Tripal, Philipp; Schneider-Stock, Regine; Kuwert, Torsten; Ocker, Matthias; Prante, Olaf (Nuclear Medicine and Biology, 2016)
Deacetylase inhibitors have recently been established as a novel therapeutic approach to solid and hematologic cancers and have also been demonstrated to possess anti-angiogenic properties. Although these compounds show a good efficacy in vitro and in vivo, no data on monitoring and predicting treatment response are currently available. We therefore investigated the effect of the pan-deacetylase inhibitor panobinostat (LBH589) on gastrointestinal cancer models and the suitability of 2-[(18)F]FGlc-RGD as a specific agent for imaging integrin ?v?3 expression during tumor angiogenesis using small animal positron emission tomography (PET).The effect of panobinostat on cell viability in vitro was assessed with a label-free impedance based real-time analysis. Nude mice bearing HT29 and HepG2 tumors were treated with daily i.p. injections of 10mg/kg panobinostat for 4weeks. During this time, tumor size was determined with a calliper and mice were repeatedly subjected to PET imaging. Tumor tissues were analyzed immunohistochemically with a focus on proliferation and endothelial cell markers (Ki-67, Meca-32) and by Western blot applying specific markers of apoptosis.In vitro, panobinostat inhibited the proliferation of HepG2 and HT29 cells. Contrary to the situation in HepG2 tumors in vivo, where panobinostat treatment is known to reduce proliferation and vascularization resulting in a decreased tumor growth, HT29 tumors did not show any effect on these parameters. We demonstrated by Western blotting, that panobinostat induced apoptosis in HT29 tumors in vivo. Longitudinal PET imaging studies in HepG2 tumor-bearing mice using 2-[(18)F]FGlc-RGD demonstrated that the standard uptake value (SUVmax) in HepG2 tumors was significantly decreased by 39% at day 7 after treatment. The comparative PET study using HT29 tumor-bearing animals did not reveal any response of the tumors to panobinostat treatment.Small-animal PET imaging using 2-[(18)F]FGlc-RGD was successfully applied to the non-invasive monitoring of the HepG2-tumor response to panobinostat in nude mice early after begin of treatment. Thus, PET imaging of angiogenesis using 2-[(18)F]FGlc-RGD could be a valuable tool to monitor panobinostat therapy in further preclinical studies.When successfully translated to the clinical surrounding, PET imaging of angiogenesis could therefore facilitate therapy planning and monitoring of therapy success with panobinostat in hepatocellular carcinoma.
EVALuna2:6737

Lipophilic cationic drugs increase the permeability of lysosomal membranes in a cell culture system - Kornhuber, Johannes; Henkel, Andreas W.; Groemer, Teja W.; Städtler, Sven; Welzel, Oliver; Tripal, Philipp; Rotter, Andrea; Bleich, Stefan; Trapp, Stefan (Journal of Cellular Physiology, 2010)
Lysosomes accumulate many drugs several fold higher compared to their extracellular concentration. This mechanism is believed to be responsible for many pharmacological effects. So far, uptake and release kinetics are largely unknown and interactions between concomitantly administered drugs often provoke mutual interference. In this study, we addressed these questions in a cell culture model. The molecular mechanism for lysosomal uptake kinetics was analyzed by live cell fluorescence microscopy in SY5Y cells using four drugs (amantadine, amitriptyline, cinnarizine, flavoxate) with different physicochemical properties. Drugs with higher lipophilicity accumulated more extensively within lysosomes, whereas a higher pKa value was associated with a more rapid uptake. The drug-induced displacement of LysoTracker was neither caused by elevation of intra-lysosomal pH, nor by increased lysosomal volume. We extended our previously developed numerical single cell model by introducing a dynamic feedback mechanism. The empirical data were in good agreement with the results obtained from the numerical model. The experimental data and results from the numerical model lead to the conclusion that intra-lysosomal accumulation of lipophilic xenobiotics enhances lysosomal membrane permeability. Manipulation of lysosomal membrane permeability might be useful to overcome, for example, multi-drug resistance by altering subcellular drug distribution. © 2010 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up

Magnetic nanoparticles for cancer therapy - Dürr, Stephan; Janko, Christina; Lyer, Stefan; Tripal, Philipp; Schwarz, Marc; Zaloga, Jan; Tietze, Rainer; Alexiou, Christoph (Nanotechnology Reviews, 2013)
Cancer is one of the biggest challenges facing the medical research in our time. The goals are to improve not only the therapeutic outcome, even in the cases of advanced and metastatic cancer, but also the methods of treatment, which often have considerable adverse effects. In addition, the current developments, such as demographic change, population growth, and increasing healthcare costs, have to be taken into consideration. In all likelihood, nanotechnology and, in particular, the use of magnetic nanoparticles consisting of the elements nickel, cobalt, and iron can make a significant contribution. The greatest potential can be ascribed to the drug delivery systems: magnetic nanoparticles are functionalized by binding them to various substances, including chemotherapeutic agents, radionuclides, nucleic acids, and antibodies. They can then be guided and accumulated using a magnetic field. Hyperthermia can be induced with an alternating magnetic field, providing another therapeutic option. Magnetic nanoparticles may be useful in overcoming cancer drug resistance. They also contribute to realizing a combination of diagnostic investigation and therapy in the field of " theranostics ". The multifaceted and promising results of research in the recent years offer the prospect of a real advance in cancer therapy in the near future.
Created from Fastlane, Scopus look-up
Keywords: Cancer drug resistance; Cancer therapy; Drug delivery; Hyperthermia; Magnetic nanoparticles

Ménage-à-Trois: The Ratio of Bicarbonate to CO2 and the pH Regulate the Capacity of Neutrophils to Form NETs - Maueröder, Christian; Mahajan, Aparna; Paulus, Susanne; Goesswein, Stefanie; Hahn, Jonas; Kienhoefer, Deborah; Biermann, Mona H.; Tripal, Philipp; Friedrich, Ralf P.; Munoz Becerra, Luis; Neurath, Markus; Becker, Christoph; et al. (Frontiers in Immunology, 2016)
In this study, we identified and characterized the potential of a high ratio of bicarbonate to CO2 and a moderately alkaline pH to render neutrophils prone to undergo neutrophil extracellular trap (NET) formation. Both experimental settings increased the rate of spontaneous NET release and potentiated the NET-inducing capacity of phorbol esters (phorbol-2-myristate-13-acetate), ionomycin, monosodium urate, and LPS. In contrast, an acidic environment impaired NET formation both spontaneous and induced. Our findings indicate that intracellular alkalinization of neutrophils in response to an alkaline environment leads to an increase of intracellular calcium and neutrophil activation. We further found that the anion channel blocker DIDS strongly reduced NET formation induced by bicarbonate. This finding suggests that the effects observed are due to a molecular program that renders neutrophils susceptible to NET formation. Inflammatory foci may be characterized by an acidic environment. Our data indicate that NET formation is favored by the higher pH at the border regions of inflamed areas. Moreover, our findings highlight the necessity for strict pH control during assays of NET formation.
EVALuna2:2182

NanoLuc Binary Technology as a methodological approach: an important new tool for studying the localization of androgen receptor and androgen receptor splice variant V7 homo and heterodimers - Guzman, Juan; Weigelt, Katrin; Neumann, Anna-Dorothea; Tripal, Philipp; Schmid, Benjamin; Winter, Zoltan; Palmisano, Ralf; Culig, Zoran; Cronauer, Marcus V.; Muschler, Paul; Wullich, Bernd; Taubert, Helge; et al. (BMC Cancer, 2024)
Background: The androgen/androgen receptor (AR)-signaling axis plays a central role in prostate cancer (PCa). Upon androgen-binding the AR dimerizes with another AR, and translocates into the nucleus where the AR-dimer activates/inactivates androgen-dependent genes. Consequently, treatments for PCa are commonly based on androgen deprivation therapy (ADT). The clinical benefits of ADT are only transitory and most tumors develop mechanisms allowing the AR to bypass its need for physiological levels of circulating androgens. Clinical failure of ADT is often characterized by the synthesis of a constitutively active AR splice variant, termed AR-V7. AR-V7 mRNA expression is considered as a resistance mechanism following ADT. AR-V7 no longer needs androgenic stimuli for nuclear entry and/or dimerization. Methods: Our goal was to mechanistically decipher the interaction between full-length AR (AR-FL) and AR-V7 in AR-null HEK-293 cells using the NanoLuc Binary Technology under androgen stimulation and deprivation conditions. Results: Our data point toward a hypothesis that AR-FL/AR-FL homodimers form in the cytoplasm, whereas AR-V7/AR-V7 homodimers localize in the nucleus. However, after androgen stimulation, all the AR-FL/AR-FL, AR-FL/AR-V7 and AR-V7/AR-V7 dimers were localized in the nucleus. Conclusions: We showed that AR-FL and AR-V7 form heterodimers that localize to the nucleus, whereas AR-V7/AR-V7 dimers were found to localize in the absence of androgens in the nucleus.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Androgen receptor; Androgen receptor variant 7; Heterodimer; Homodimer; NanoLuc Binary Technology; Prostate cancer

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Pathological function of neutrophil extracellular traps in human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Tripal, Philipp; Geppert, Carol-Immanuel; Merkel, Susanne; Herrmann, Martin; Stürzl, Michael (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Permeability analyses and three dimensional imaging of interferon gamma-induced barrier disintegration in intestinal organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Schmid, Benjamin; Waldner, Maximilian; Naschberger, Elisabeth; Scharl, Michael; Mueller, Werner; Günther, Claudia; Becker, Christoph; Stürzl, Michael; Tripal, Philipp (Stem Cell Research, 2019)
The aberrant regulation of the epithelial barrier integrity is involved in many diseases of the digestive tract, including inflammatory bowel diseases and colorectal cancer. Intestinal epithelial cell organoid cultures provide new perspectives for analyses of the intestinal barrier in vitro. However, established methods of barrier function analyses from two dimensional cultures have to be adjusted to the analysis of three dimensional organoid structures. Here we describe the methodology for analysis of epithelial barrier function and molecular regulation in intestinal organoids. Barrier responses to interferon-y of intestinal organoids with and without epithelial cellspecific deletion of the interferon-y-receptor 2 gene were used as a model system. The established method allowed monitoring of the kinetics of interferon-y-induced permeability changes in living organoids. Proteolytic degradation and altered localization of the tight junction proteins claudin-2, -7, and - 15 was detected using confocal spinning disc microscopy with 3D reconstruction. Hessian analysis was used for quantification of relocalization of claudins. In summary, we provide a novel methodologic approach for quantitative analyses of intestinal epithelial barrier functions in the 3D organoid model.
CRIS-Team WoS Importer:2019-03-12

Photoinducible penetration enhancement and drug release for cancer treatment - Cicha, Iwona; Lyer, Stefan; Dürr, Stephan; Schwarz, Marc; Tietze, Rainer; Tripal, Philipp; Alexiou, Christoph (Nanomedicine, 2014)
EVALuna2:19949

Pre-incubation of corneal donor tissue with sCD83 improves graft survival via the induction of alternatively activated macrophages and tolerogenic dendritic cells - Peckert-Maier, Katrin; Schoenberg, Alfrun; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Stich, Lena; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix (American Journal of Transplantation, 2021)
Immune responses reflect a complex interplay of cellular and extracellular components which define the microenvironment of a tissue. Therefore, factors that locally influence the microenvironment and re-establish tolerance might be beneficial to mitigate immune-mediated reactions, including the rejection of a transplant. In this study, we demonstrate that pre-incubation of donor tissue with the immune modulator soluble CD83 (sCD83) significantly improves graft survival using a high-risk corneal transplantation model. The induction of tolerogenic mechanisms in graft recipients was achieved by a significant upregulation of Tgfb, Foxp3, II27, and II10 in the transplant and an increase of regulatory dendritic cells (DCs), macrophages (M phi) and T cells (Tregs) in eye-draining lymph nodes. The presence of sCD83 during in vitro DC and M phi generation directed these cells toward a tolerogenic phenotype leading to reduced proliferation-stimulating activity in MLRs. Mechanistically, sCD83 induced a tolerogenic M phi and DC phenotype, which favors Treg induction and significantly increased transplant survival after adoptive cell transfer. Conclusively, pre-incubation of corneal grafts with sCD83 significantly prolongs graft survival by modulating recipient M phi and DCs toward tolerance and thereby establishing a tolerogenic microenvironment. This functional strategy of donor graft pre-treatment paves the way for new therapeutic options in the field of transplantation.
CRIS-Team WoS Importer:2021-10-01

Pre-incubation of corneal donor tissue with soluble CD83 improves graft survival via the induction of pro-resolving macrophages - Peckert-Maier, Katrin; Schoenberg, Alfrun; Wild, Andreas; Royzman, Dmytro; Braun, Gabriele; Hadrian, Karina; Tripal, Philipp; Cursiefen, Claus; Steinkasserer, Alexander; Zinser, Elisabeth; Bock, Felix (WOUND REPAIR AND REGENERATION, 2022)
CRIS-Team WoS Importer:2022-09-16

Processing and secretion of guanylate binding protein-1 depend on inflammatory caspase activity - Naschberger, Elisabeth; Geissdorfer, Walter; Bogdan, Christian; Tripal, Philipp; Kremmer, Elisabeth; Stürzl, Michael; Britzen-Laurent, Nathalie (Journal of Cellular and Molecular Medicine, 2017)
Human guanylate binding protein-1 (GBP-1) belongs to the family of large GTPases. The expression of GBP-1 is inducible by inflammatory cytokines, and the protein is involved in inflammatory processes and host defence against cellular pathogens. GBP-1 is the first GTPase which was described to be secreted by eukaryotic cells. Here, we report that precipitation of GBP-1 with GMP-agarose from cell culture supernatants co-purified a 47-kD fragment of GBP-1 (p47-GBP-1) in addition to the 67-kD full-length form. MALDI-TOF sequencing revealed that p47-GBP-1 corresponds to the C-terminal helical part of GBP-1 and lacks most of the globular GTPase domain. In silico analyses of protease target sites, together with cleavage experiments in vitro and in vivo, showed that p67-GBP-1 is cleaved by the inflammatory caspases 1 and 5, leading to the formation of p47-GBP-1. Furthermore, the secretion of p47-GBP-1 was found to occur via a non-classical secretion pathway and to be dependent on caspase-1 activity but independent of inflammasome activation. Finally, we showed that p47-GBP-1 represents the predominant form of secreted GBP-1, both in cell culture supernatants and, in vivo, in the cerebrospinal fluid of patients with bacterial meningitis, indicating that it may represent the biologically active form of extracellular GBP-1. These findings confirm the involvement of caspase-1 in non-classical secretion mechanisms and open novel perspectives for the extracellular function of secreted GBP-1.
EVALuna2:7752

Prototypic (18)F-Labeled Argininamide-Type Neuropeptide Y Y1R Antagonists as Tracers for PET Imaging of Mammary Carcinoma - Keller, Max; Maschauer, Simone; Brennauer, Albert; Tripal, Philipp; Koglin, Norman; Dittrich, Ralf; Bernhardt, Guenther; Kuwert, Torsten; Wester, Hans-Juergen; Buschauer, Armin; Prante, Olaf (ACS Medicinal Chemistry Letters, 2017)
The neuropeptide Y (NPY) Y1 receptor (Y1R) selective radioligand (R)-N(?)-(2,2-diphenylacetyl)-N(?)-[4-(2-[(18)F]fluoropropanoylamino)butyl]aminocarbonyl-N-(4-hydroxybenzyl)argininamide ([(18)F]23), derived from the high-affinity Y1R antagonist BIBP3226, was developed for imaging studies of Y1R-positive tumors. Starting from the argininamide core bearing amine-functionalized spacer moieties, a series of fluoropropanoylated and fluorobenzoylated derivatives was synthesized and studied for Y1R affinity. The fluoropropanoylated derivative 23 displayed high affinity (Ki = 1.3 nM) and selectivity toward Y1R. Radiosynthesis was accomplished via (18)F-fluoropropanoylation, yielding [(18)F]23 with excellent stability in mice; however, the biodistribution study revealed pronounced hepatobiliary clearance with high accumulation in the gall bladder (>100 %ID/g). Despite the unfavorable biodistribution, [(18)F]23 was successfully used for imaging of Y1R positive MCF-7 tumors in nude mice. Therefore, we suggest [(18)F]23 as a lead for the design of PET ligands with optimized physicochemical properties resulting in more favorable biodistribution and higher Y1R-dependent enrichment in mammary carcinom
EVALuna2:13870

Reconfiguration and loss of peritubular capillaries in chronic kidney disease. - Gaupp, Charlotte; Schmid, Benjamin; Tripal, Philipp; Edwards, Aurélie; Daniel, Christoph; Zimmermann, Stefan; Goppelt-Strübe, Margarete; Willam, Carsten; Rosen, Seymour; Schley, Gunnar (Scientific Reports, 2023)
Functional and structural alterations of peritubular capillaries (PTCs) are a major determinant of chronic kidney disease (CKD). Using a software-based algorithm for semiautomatic segmentation and morphometric quantification, this study analyzes alterations of PTC shape associated with chronic tubulointerstitial injury in three mouse models and in human biopsies. In normal kidney tissue PTC shape was predominantly elongated, whereas the majority of PTCs associated with chronic tubulointerstitial injury had a rounder shape. This was reflected by significantly reduced PTC luminal area, perimeter and diameters as well as by significantly increased circularity and roundness. These morphological alterations were consistent in all mouse models and human kidney biopsies. The mean circularity of PTCs correlated significantly with categorized glomerular filtration rates and the degree of interstitial fibrosis and tubular atrophy (IFTA) and classified the presence of CKD or IFTA. 3D reconstruction of renal capillaries revealed not only a significant reduction, but more importantly a substantial simplification and reconfiguration of the renal microvasculature in mice with chronic tubulointerstitial injury. Computational modelling predicted that round PTCs can deliver oxygen more homogeneously to the surrounding tissue. Our findings indicate that alterations of PTC shape represent a common and uniform reaction to chronic tubulointerstitial injury independent of the underlying kidney disease.
EVALuna2:561937

Role of IFN-gamma-activation of distinct tumor and stromal cell populations in colorectal carcinoma pathogenesis - Britzen-Laurent, Nathalie; Guo, Wei; Langer, Victoria; Khoziainova, Svetlana; Weisenburger, Thomas; Winkler, Thomas; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Naschberger, Elisabeth; Skottke, Lisa; Tripal, Philipp; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

ROS-Responsive N-Alkylaminoferrocenes for Cancer-Cell-Specific Targeting of Mitochondria - Reshetnikov, Viktor; Daum, Steffen; Janko, Christina; Karawacka, Weronika; Tietze, Rainer; Alexiou, Christoph; Paryzhak, Solomiya; Dumych, Tetiana; Bilyy, Rostyslav; Tripal, Philipp; Schmid, Benjamin; Palmisano, Ralf; et al. (Angewandte Chemie International Edition, 2018)
Mitochondrial membrane potential is more negative in cancer cells than in normal cells, allowing cancer targeting by delocalized lipophilic cations (DLCs). However, as the difference is rather small, these drugs affect also normal cells. Now a concept of pro-DLCs is proposed based on an N-alkylaminoferrocene structure. These prodrugs are activated by the reaction with reactive oxygen species (ROS) forming ferrocenium-based DLCs. Since ROS are overproduced in cancer, the high-efficiency cancer-cell-specific targeting of mitochondria could be achieved as demonstrated by fluorescence microscopy in combination with two fluorogenic pro-DLCs in vitro and in vivo. We prepared a conjugate of another pro-DLC with a clinically approved drug carboplatin and confirmed that its accumulation in mitochondria was higher than that of the free drug. This was reflected in the substantially higher anticancer effect of the conjugate.
EVALuna2:35451

Synthesis and characterization of a new two photon excitable acid sphingomyelinase FRET probe - Mohamed, Zain H.; Rhein, Cosima; Schmid, Benjamin; Tripal, Philipp; Kornhuber, Johannes; Arenz, Christoph (Bioorganic & medicinal chemistry, 2021)
Recently, FRET probes for acid sphingomyelinase (ASM) have enabled the observation of enzyme activity in intact cells for the first time. Here we present an ASM FRET probe specifically optimized for 2-photon excitation. To facilitate probe characterization and comparison to the previous probe, we mixed the two intact probes with defined amounts of the probes' ceramide cleavage products and mounted them on lipid beads. Directly excited NBD FRET acceptor fluorescene proved to be a useful means of reference and showed that the new probe is brighter, albeit only moderately, than the previous one. The new probe was then used to detect inhibition by various ASM inhibitors microscopically for the first time. Also in cells, directly excited acceptor fluorescence proved to be a useful parameter in addition to FRET to visualize inhibition of ASM.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Antidepressants; Enzyme inhibitors; FRET probes; Förster resonance energy transfer (FRET); Sphingolipids; Two-photon microscopy

The role of ceramide in major depressive disorder - Kornhuber, Johannes; Reichel, Martin; Tripal, Philipp; Groemer, Teja W.; Henkel, Andreas W.; Mühle, Christiane; Gulbins, Erich (European archives of psychiatry and clinical neuroscience, 2009)
Major depression is a severe mood disorder with a lifetime prevalence of more than 10%. The pharmacokinetic hypothesis claims that a slow accumulation of antidepressant drugs by acid trapping mainly into lysosomes is responsible for the therapeutic latency and that a lysosomal target mediates the antidepressant effects. The lysosomal lipid metabolizing enzyme acid sphingomyelinase (ASM) cleaves sphingomyelin into ceramide and phosphorylcholine. In a pilot study, the activity of this enzyme was increased in peripheral blood cells of patients with major depressive disorder (MDD), making the ASM an interesting molecular target of antidepressant drugs. Indeed, several antidepressant drugs functionally inhibit ASM. The ASM/ceramide pathway might be a missing link unifying independent findings in neurobiology and the treatment of MDD such as therapeutic latency, oxidative stress, immune activation and increased risk of cardiovascular disease. © 2009 Springer-Verlag.
Created from Fastlane, Scopus look-up
Keywords: Acid sphingomyelinase; Amitriptyline; Ceramide; Fluoxetine; Lysosomes; Major depressive disorder; Neuroplasticity hypothesis; Pharmacokinetic hypothesis; Sphingolipids

Treatment with Cyclic AMP Activators Reduces Glioblastoma Growth and Invasion as Assessed by Two-Photon Microscopy - Wartchow, Krista Mineia; Schmid, Benjamin; Tripal, Philipp; Stadlbauer, Andreas; Buchfelder, Michael; Goncalves, Carlos-Alberto; Kleindienst, Andrea (Cells, 2021)
(1) Background: Despite progress in surgery and radio-chemotherapy of glioblastoma (GB), the prognosis remains very poor. GB cells exhibit a preference for hypoxia to maintain their tumor-forming capacity. Enhancing oxidative phosphorylation-known as the anti-Warburg effect-with cyclic AMP activators has been demonstrated to drive GB cells from proliferation to differentiation thereby reducing tumor growth in a cell culture approach. Here we re-evaluate this treatment in a more clinically relevant model. (2) Methods: The effect of treatment with dibutyryl cyclic AMP (dbcAMP, 1 mM) and the cAMP activator forskolin (50µM) was assessed in a GB cell line (U87GFP+, 104 cells) co-cultured with mouse organotypic brain slices providing architecture and biochemical properties of normal brain tissue. Cell viability was determined by propidium-iodide, and gross metabolic effects were excluded in the extracellular medium. Tumor growth was quantified in terms of area, volume, and invasion at the start of culture, 48 h, 7 days, and 14 days after treatment. (3) Results: The tumor area was significantly reduced following dbcAMP or forskolin treatment (F2,249 = 5.968, p = 0.0029). 3D volumetric quantification utilizing two-photon fluorescence microscopy revealed that the treated tumors maintained a spheric shape while the untreated controls exhibited the GB typical invasive growth pattern. (4) Conclusions: Our data demonstrate that treatment with a cAMP analog/activator reduces GB growth and invasion.
CRIS-Team Scopus Importer:2021-04-16
Keywords: 2-photon-microscopy; glioblastoma; oxidative phosphorylation; treatment; Warburg effect

Ultra-smooth and space-filling mineral films generated via particle accretion processes - Harris, Joseph; Mey, Ingo P.; Böhm, Corinna; Trinh, Huyen; Leupold, Simon; Prinz, Carsten; Tripal, Philipp; Palmisano, Ralf; Wolf, Stephan (Nanoscale Horizons, 2019)
Nonclassical crystallization typically yields materials with pronounced roughness and porosity as it is driven by nanoparticle self-organization. Here, we demonstrate that bio-inspired nonclassical mineralization via magnesium-doped polymer-induced liquid precursors (PILP) can yield ultra-smooth and space-filling CaCO3 films featuring an unprecedented low roughness of 0.285 nm.
CRIS-Team WoS Importer:2019-11-01

Unique features of different members of the human guanylate-binding protein family - Tripal, Philipp; Bauer, Michael; Naschberger, Elisabeth; Mörtinger, Thomas; Hohenadl, Christine; Cornali, Emmanuelle; Thurau, Mathias; Stürzl, Michael (Journal of Interferon and Cytokine Research, 2007)
Guanylate-binding proteins (GBPs) are the most abundant cellular proteins expressed in response to interferon-γ (IFN-γ), with seven highly homologous members in humans, termed HuGBP-1 to HuGBP-7. To date, differential features that may indicate differential functions of these proteins have not been described. Here, we investigated the expression and subcellular localization of the different HuGBPs in endothelial cells (EC). IFN-γ, tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) induced the expression of HuGBP-1, HuGBP-2, and HuGBP-3 at similar high levels. In contrast, expression of HuGBP-4 and HuGBP-5 was robustly induced only by IFN-γ and not by TNF-α and IL-1β. Expression of HuGBP-6 and HuGBP-7 was not detected in EC under the various conditions examined. Investigating subcellular localization of the EC-expressed HuGBPs, HuGBP-1, HuGBP-3, and HuGBP-5 were exclusively detected in the cytoplasm, whereas HuGBP-2 and HuGBP-4 displayed a nucleocytoplasmic distribution. Treatment of the cells with IFN-γ and aluminum fluoride caused rapid enrichment of HuGBP-1 and HuGBP-2 in the Golgi apparatus, as demonstrated by time-lapse microscopy and fluorescence analyses of GFP-tagged HuGBPs. HuGBP-3 and HuGBP-4 were never detected in the Golgi apparatus, whereas HuGBP-5 was constitutively enriched in this cytosolic compartment, irrespective of stimulation. These results assign a characteristic pattern of expression and subcellular localization to each of the HuGBPs, indicating for the first time that these proteins may have different cellular functions. © Mary Ann Liebert, Inc.
Created from Fastlane, Scopus look-up